Sustainable Buildings for the High North. Energy performance of current building stock in Scandinavia and Russia - Sirviö, Anu; Illikainen, Kimmo (Oulun ammattikorkeakoulu, 2015)
Worldwide, buildings are responsible for one-third of the total final energy consumption, and are among most significant creators of carbon dioxide emissions. Due to constantly increasing prices of energy and changing environmental circumstances, more emphasis is given on the discovery of energy efficient solutions. Exploitation of energy efficient technological solutions and renewable energy sources provide environmental friendly and cost-effective alternatives also for renovation of buildings and living. Local infrastructure as well as directives, laws and standards set by the European Union and governments guide energy performance of buildings and implementation of renovations. By adjusting and unifying regulations, the challenges of cold climate could be encountered in sustainable manner and cross-border trade accelerated in the high north, where vast resources are available. In this report, building stock, renovation status, energy production and usage are discussed in Finland, Sweden, Norway and Russia. The work is mainly done for the purposes of the SBHN-project. The goals of the Sustainable Buildings for the High North (SBHN) -project are to discover arctic climate- adjusted methods to improve energy efficiency of residential apartment buildings and to enhance cross-border trade between Scandinavian countries and Russia. The results of the project are expected to promote various business opportunities and the development of close co-operation between the northern countries in the fields of building technology industry, innovative research and education among companies, universities, colleges and the authorities.